Risk factors and outcomes for multidrug-resistant Gram-negative bacilli bacteremia. (January 2018) - Patolia, Swati; Abate, Getahun; Patel, Nirav; Patolia, Setu; Frey, Sharon
Background: The incidence of multidrug-resistant (MDR) organisms is increasing along with mortality. Identifying risk factors for the development of MDR Gram-negative bacilli (GNB) bacteremia could greatly impact patient care and management. Methods: Data from the electronic health record of patients with GNB over 13-month period were collected at a single university medical center. Baseline demographic data, risk factor, microbiological data, recurrence of bacteremia, and mortality were recorded. Results: A total of 177 patients were included in the analysis. MDR GNB occurred in 46 patients (26%). The mortality rate in the MDR group was 34.8% compared to 13.7% in non-MDR group ( p = 0.002). In multivariate analysis, diabetes mellitus [DM; odds ratio (OR): 2.8, 95% confidence interval (CI): 1–4.88], previous antibiotic use (OR: 2.93, 95% CI: 1.25–6.87), and urinary catheter as a source of infection (OR 5.96, 95% CI: 1.78–19.94) were significant risk factors for the development of MDR GNB. In addition, end-stage liver disease (OR: 3.64, 95% CI: 1.07–12.3), solid organ malignancy (OR: 3.64, 95% CI: 1.25–10.56), intra-abdominal source of infection (OR: 3.66, 95% CI: 1.14–11.73), inappropriate empiric antibiotics (OR 7.59, 95% CI: 1.68–34.34) and urinary catheter as a source of infection (OR 5.68, 95% CI: 1.37–23.5) were significant factors for mortality in patients with MDR GNB. Conclusion: Our study provides important information about the risk factors for the development of MDR GNB bacteremia and helps prognosticate patient with MDR GNB.